Experimental Comparison of HfO2/X-Based ReRAM Devices Switching Properties by the MIM Capacitance - Fernando Jose da Costa; Aseel Zeinati; Renan Trevisoli; Durga Misra; Rodrigo Trevisoli Doria (IEEE Journal of the Electron Devices Society)
The objective of this work is to present a comparison of the switching properties in Resistive Random-Access-Memory between two different switching layer devices through the capacitance measurements. The analysis was carried out in two devices with different insulating layers, one composed of H-plasma-treated ${ HfO}_{2}$ and another with a stoichiometric HfO2. The device with a higher quantity of oxygen vacancy-related defects in the insulator (HfO2 w/trt) presents a wider spread of the capacitance with the application of a range of varying pulse widths. An increase in the capacitance from 3.904 to 3.917 pF/ $μ $ m2 was observed for the same device when it was subjected to a $144~μ $ s pulse width, demonstrating a conductance quantization required for the application in in-memory computing systems. Also, the dielectric constant modulates due to the migration of oxygen atoms inside the device’s insulator.